MOTIVASI KERJA PEGAWAI APARATUR SIPIL NEGARA (ASN) PADA DINAS PEMUDA DAN OLAHRAGA PROVINSI RIAU - Meri Septiani; Nurmasari Nurmasari (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2019)
This research aim to to know how motivation work Officer Of Aparatur Civil State (ASN) at Department Youth and Athletics of Provinsi Riau. Indicator assessment of utilized by work motivation is covering internal motivation and motivation of Externall. Research type which is have location to in Office Department Youth and Athletics of Provinsi this Riau is diskriptif survey, that is priority enlist Questioner as a means of compiler of gathered data and data by means of is later made by especial raw material to analyse empirical kondiisi of obyektivitas existence of research target at accurate location. There are one group at this research that is Officer Of Aparatur Civil State (ASN) amount to 57 people. Sampling technique which is utilized in specifying individual of sampel is technique of purposive type sampling and used to data collecting technique consist of, primary data collected by using technique enlist interview and kuesioner and also data of sekunder collected use observation technique. Pursuant to result of Summary Comments Answer Responder Concerning Indicator Motivation Work Officer Of Aparatur Civil State (ASN) at Department Youth and Athletics of Provinsi Riau. From the mentioned can be pulled by a conclusion that for this research in categorize High with percentage 53% as according to previous clarification about measurement of percentage equal to 34% - 66% included in category Medium.